2012
DOI: 10.1074/jbc.m112.342030
|View full text |Cite
|
Sign up to set email alerts
|

Oligonucleotide Models of Telomeric DNA and RNA Form a Hybrid G-quadruplex Structure as a Potential Component of Telomeres

Abstract: Background: Telomeric repeat-containing RNA has recently been found in mammalian cells. Results: Oligonucleotide models of telomeric DNA and RNA form a hybrid G-quadruplex structure. Conclusion: We suggest a model system for understanding the structure and function of human telomeres. Significance: Our finding provides valuable information for understanding the structure and function of human telomeric DNA and RNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
41
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 51 publications
6
41
0
Order By: Relevance
“…This is a general phenomenon rather than a situation associated to a specific sequence. Synthetic G-rich DNA and RNA oligomer forms HQ when they are mixed and incubated together (9,10), or delivered together into cells (35). With all the techniques available to us to identify the structure, our results show that HQ also forms in a dynamic physiological process.…”
Section: Resultsmentioning
confidence: 99%
“…This is a general phenomenon rather than a situation associated to a specific sequence. Synthetic G-rich DNA and RNA oligomer forms HQ when they are mixed and incubated together (9,10), or delivered together into cells (35). With all the techniques available to us to identify the structure, our results show that HQ also forms in a dynamic physiological process.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence in support of this idea includes the observation that a fraction of TERRA remains associated with telomeric chromatin (Azzalin et al 2007;Schoeftner and Blasco 2008;Deng et al 2009) and dysfunction of the Rat1 ribonuclease leads to TERRA accumulation and telomere elongation defects in S. cerevisiae, both phenotypes being suppressed by RNase H overexpression (Luke et al 2008). Furthermore, both telomeric DNA and TERRA adopt G4-DNA structures (Phan 2010;Xu et al 2010;Lu et al 2013), and RNA-DNA hybrid G4 structures may represent a telomere component according to recent modeling studies (Xu et al 2012a). The existence of telomeric R-loops has been recently shown in budding yeast in two independent studies.…”
mentioning
confidence: 93%
“…1,2 Human telomeric RNA performs various biofunctions, such as the regulation of the telomere length, 312 heterochromatin formation, 13,14 and end protection. 15,16 Recent studies suggest that telomeric RNA forms a G-quadruplex that plays an important role in telomere protection and regulation. 3,16,17 We and others have shown that human telomeric RNA forms G-quadruplex structures.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Recent studies suggest that telomeric RNA forms a G-quadruplex that plays an important role in telomere protection and regulation. 3,16,17 We and others have shown that human telomeric RNA forms G-quadruplex structures. 1824 Additionally, we have demonstrated that telomeric RNA G-quadruplex structures play an important role in providing a protective structure to the telomere ends.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation